Measuring Neuroticism in Nepali: Reliability and Validity of the Neuroticism Subscale of the Eysenck Personality Questionnaire - Manandhar, K.; Risal, A.; Linde, M.; Koju, R.; Steiner, T.J.; Holen, A. (Kathmandu University Medical Journal, 2017)
Background The Neuroticism subscale of the Eysenck Personality Questionnaire Revised Short Form (12 items) (EPQRS-N) has proven to be a reliable and valid measure in multiple languages.Objective To develop a single-factor Nepali-language version of the EPQRS-N for use in the adult population of Nepal.Method The original English version of EPQRS-N was translated into Nepali using a forward-backward translation protocol. The first set of translated items was modified after testing by factor analysis with principal component extraction in an outpatient sample. Items with low factor correlations or poor semantic consistencies were reworded to fit the gist of the original items in a Nepali cultural context; the revised version was then tested in a representative random sample from the general population. Again, the same statistical procedures were applied.Results The first trial gave three factors. Based on the factor distribution of the items or their semantic quality, five were reworded. In the second trial, a two-factor solution emerged; the second factor had only one item with high correlation, which also had modest correlation with the first factor. Accordingly, a forced one-factor solution was chosen. This gave an internal consistency (Cronbach’s alpha) of 0.80, with item-to-factor correlations from 0.40 to 0.73, and item-to-sum correlations from 0.31 to 0.61.Conclusion The final Nepali version of EPQRS-N achieved satisfactory internal consistency. The item distribution coincided with the original English version, providing acceptable construct validity. It is psychometrically adequate for use in capturing the personality trait of neuroticism, and has broad applicability to the adult population of Nepal because of the diversity of the participant samples in which it was developed.